Monodispersed sub-5.0 nm PtCu nanoalloys as enhanced bifunctional electrocatalysts for oxygen reduction reaction and ethanol oxidation reaction. Issue 9 (17th February 2017) - Liu, Taiyang; Wang, Kai; Yuan, Qiang; Shen, Zebin; Wang, Ye; Zhang, Qinghong; Wang, Xun
Abstract : Monodispersed, uniform sub-5.0 nm PtCu alloy polyhedra have been obtained through a one-pot route. These PtCu polyhedra show enhanced catalytic properties toward ORR and EOR. Abstract : The development of effective electrocatalysts with enhanced activity and stability for both the anode and the cathode reaction in fuel cells still remains a challenge. Here, we report a one-pot route to prepare monodispersed, uniform sub-5.0 nm PtCu alloy polyhedra with a narrow size distribution. These PtCu alloy polyhedra exhibit enhanced electrocatalytic activity for both cathode and anode reactions as compared to the commercial Pt/C catalyst under alkaline conditions. The specific activity and mass activity on Pt68 Cu32 nanoalloys are 15 and 2.8 times that on Pt/C catalyst toward oxygen reduction reaction (ORR), respectively. And the peak current density and mass activity on Pt68 Cu32 nanoalloys are 11.8 and 2.12 times that on Pt/C catalyst toward ethanol oxidation reaction (EOR), respectively. Furthermore, the as-synthesized Pt68 Cu32 nanoalloys have much higher stability than commercial Pt/C black for both ORR and EOR. These experimental results show an effective approach to the development of monodispersed, sub-5.0 nm PtCu nanoalloys as bifunctional electrocatalysts for both the cathode and the anode reaction in fuel cells.